2007
DOI: 10.1111/j.1365-2125.2007.03039.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CYP2C19 polymorphism on nelfinavir to M8 biotransformation in HIV patients

Abstract: What is already known about this subject • Nelfinavir is an HIV protease inhibitor, substrate of the transporter P‐glycoprotein and metabolized via CYP2C19, CYP3A4 and CYP3A5 enzymes. • Pharmacokinetic studies have shown wide interindividual variability of nelfinavir concentrations, some of this variability perhaps caused by variant drug metabolism or transporter genes. • For CYP3A4*1B and CYP3A5*3 polymorphism, results from three studies are in agreement, showing no difference in nelfinavir concentrations be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…A recent study found that patients (n=166) on escitalopram therapy, carrying the CYP2C19*17 allele (UM phenotype) exhibited 42 % lower plasma concentrations than those homozygous for CYP2C19*1 and underlined the necessity of dose adjustment (123). The rate of nelfi navir (for HIV treatment) biotransformation to M8 was reduced by 50 % in patients with the CYP2C19*1/*2 or *2/*2 genotype compared to those with the *1/*1 genotype, with consequences of modifi ed short-term effi cacy and toxicity and fi nal virological response (124). Some reports documented that the CYP2C19*2 loss-of-function polymorphism was associated with an increased treatment-related mortality (TRM) in patients undergoing allogenic transplantation (125).…”
Section: Cyp2c19mentioning
confidence: 95%
“…A recent study found that patients (n=166) on escitalopram therapy, carrying the CYP2C19*17 allele (UM phenotype) exhibited 42 % lower plasma concentrations than those homozygous for CYP2C19*1 and underlined the necessity of dose adjustment (123). The rate of nelfi navir (for HIV treatment) biotransformation to M8 was reduced by 50 % in patients with the CYP2C19*1/*2 or *2/*2 genotype compared to those with the *1/*1 genotype, with consequences of modifi ed short-term effi cacy and toxicity and fi nal virological response (124). Some reports documented that the CYP2C19*2 loss-of-function polymorphism was associated with an increased treatment-related mortality (TRM) in patients undergoing allogenic transplantation (125).…”
Section: Cyp2c19mentioning
confidence: 95%
“…We have considered the possible effects of co-occurrence of HIV infection in the MMT patients in this study because several HIV medications are known to inhibit the enzymatic activities of CYP2C19 and 3A4 (Burger et al, 2006;Hirt et al, 2008), thus would affect the metabolism of methadone (Ward et al, 2003). In fact, only three subjects in the present cohort had been treated with HIV medications.…”
Section: Cyp2c19 Gene In Methadone Maintenancementioning
confidence: 99%
“…Since AZT and 3TC are orally administered, the k a of AZT, the Tk0 of 3TC, CL/F, and V/F were identifiable. Concerning metabolites, since no urinary concentrations were available, only the parameters (CL m /F)/k m and (V m /F)/k m were identifiable (21,29). We could thus determine k em as the ratio of both previous parameters and also the half-lives of the parent drugs and metabolites.…”
Section: Methodsmentioning
confidence: 99%
“…Patients received a combination of two NRTIs plus one PI as antiretroviral therapy. Population PK analyses of the data from the nelfinavir group and the ritonavir-boosted indinavir group obtained in this trial were performed to evaluate the impact of genetic polymorphisms on nelfinavir and indinavir pharmaco-kinetics (PK) and the link between concentrations and shortterm efficacy (10,21). A substudy of the COPHAR2-ANRS111 trial consisted of measuring plasma and intracellular concentrations of AZT and 3TC in patients whose treatment contained AZT and 3TC as NRTIs with a PI.…”
mentioning
confidence: 99%